Mosaic in Painting as a Medium for Developing Creativity - Andiko Putra; Irwan Irwan; Iswandi Iswandi; Suci Fajrina; Rosta Minawati (Gorga : Jurnal Seni Rupa, 2026)
This research is a literature review that aims to explore the mosaic technique as a form of fine art expression that emphasizes the combination of colors, shapes, and textures in creating aesthetic value, as well as a means of developing students' creativity. Mosaic is a technique of arranging small pieces of materials such as paper, glass, or ceramics into a complete and harmonious image. In the context of art education, this technique not only functions as a medium of expression, but also as a vehicle for fostering students' creativity, imagination, and visual thinking skills. The method used in this research is a literature review, namely a systematic study of various research results, books, and scientific articles that discuss the application of mosaic techniques in fine art learning and the development of creativity. Data were collected through searching various relevant literature sources, then analyzed descriptively to identify key findings related to the benefits of mosaic techniques in art learning. The results of the study indicate that the application of mosaic techniques has great potential in improving students' creativity, accuracy, patience, and aesthetic sensitivity. Working with mosaics provides an opportunity for students to experiment freely with color, shape, and composition, while simultaneously fostering an appreciative attitude towards works of art. Thus, the mosaic technique can be used as an alternative strategy for learning fine arts that is effective and meaningful for developing students' creative potential.